Academic potential and cognitive functioning of long‐term survivors after childhood liver transplantation. (20th March 2014) - Ee, L. C.; Lloyd, O.; Beale, K.; Fawcett, J.; Cleghorn, G. J.
Abstract This cross‐sectional study assessed intellect, cognition, academic function, behaviour, and emotional health of long‐term survivors after childhood liver transplantation. Eligible children were >5 yr post‐transplant, still attending school, and resident in Queensland. Hearing and neurocognitive testing were performed on 13 transplanted children and six siblings including two twin pairs where one was transplanted and the other not. Median age at testing was 13.08 (range 6.52–16.99) yr; time elapsed after transplant 10.89 (range 5.16–16.37) yr; and age at transplant 1.15 (range 0.38–10.00) yr. Mean full‐scale IQ was 97 (81–117) for transplanted children and 105 (87–130) for siblings. No difficulties were identified in intellect, cognition, academic function, and memory and learning in transplanted children or their siblings, although both groups had reduced mathematical ability compared with normal. Transplanted patients had difficulties in executive functioning, particularly in self‐regulation, planning and organization, problem‐solving, and visual scanning. Thirty‐one percent (4/13) of transplanted patients, and no siblings, scored in the clinical range for ADHD. Emotional difficulties were noted in transplanted patients but were not different from their siblings. Long‐term liver transplant survivors exhibit difficulties in executive function and are more likely to have ADHD despite relatively intact intellect and cognition.